FOSTERING LANGUAGE LEARNER AUTONOMY THROUGH THE INVOLVEMENT OF ICT: TEACHERS’ PERCEPTION - Aji Budi Rinekso; Eri Kurniawan (ELTR Journal, 2020)
Learner autonomy has become a key issue in promoting effective language teaching. Besides, ICT has contributed to the betterment of English language teaching. In fact, there is still limited research which focuses on investigating English teachers’ perception on the use of ICT to promote learner autonomy. This study aimed to investigate the English teachers’ perception on the involvement of ICT for promoting learner autonomy. A Qualitative research design was employed in this study. The data were collected through online questionnaires and interviews. Thirty English teachers were voluntarily involved to participate in this research. The results of the study revealed that the majority of the English teachers saw ICT as an opportunity for them to promote learner autonomy since it helped the students to be more independent and engaged with the lessons. Further research focusing on students’ perspectives about learner autonomy was suggested to enrich the literature of language learner autonomy.